2011
DOI: 10.1371/journal.pone.0023973
|View full text |Cite
|
Sign up to set email alerts
|

One Carbon Metabolism in SAR11 Pelagic Marine Bacteria

Abstract: The SAR11 Alphaproteobacteria are the most abundant heterotrophs in the oceans and are believed to play a major role in mineralizing marine dissolved organic carbon. Their genomes are among the smallest known for free-living heterotrophic cells, raising questions about how they successfully utilize complex organic matter with a limited metabolic repertoire. Here we show that conserved genes in SAR11 subgroup Ia (Candidatus Pelagibacter ubique) genomes encode pathways for the oxidation of a variety of one-carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
258
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(279 citation statements)
references
References 80 publications
8
258
0
1
Order By: Relevance
“…One of the surprises of Pelagibacter metabolism was the discovery that they devote part of their genome to one-carbon (C1) metabolism. C1 metabolism enables Pelagibacterales to oxidize a broad range of external metabolites, including C1 compounds, such as methanol and formaldehyde, and methylated compounds, including osmolytes (glycine betaine, taurine, 3-dimethyl-sulfoniopropionate and trimethylamine oxide; Sun et al, 2011). Osmolytes, also known as compatible solutes, are fundamental compounds in the sense that they are produced in large amounts by all cells in marine systems.…”
Section: Living Streamlinedmentioning
confidence: 99%
“…One of the surprises of Pelagibacter metabolism was the discovery that they devote part of their genome to one-carbon (C1) metabolism. C1 metabolism enables Pelagibacterales to oxidize a broad range of external metabolites, including C1 compounds, such as methanol and formaldehyde, and methylated compounds, including osmolytes (glycine betaine, taurine, 3-dimethyl-sulfoniopropionate and trimethylamine oxide; Sun et al, 2011). Osmolytes, also known as compatible solutes, are fundamental compounds in the sense that they are produced in large amounts by all cells in marine systems.…”
Section: Living Streamlinedmentioning
confidence: 99%
“…Interestingly, several surface stations (ST 4, 5, 8 and 1) displayed CH 4 saturation levels as high as 650%. Although it remains unclear at present how CH 4 is formed in sea ice, it is possible that CH 4 could be produced via the methylotrophic pathway mediated by methylated compounds (Schäfer, 2007;Sun et al, 2011). One candidate for methylated compounds is DMSP and/or DMS, as indicated in the surface water by Damm et al (2010) and Florez-Leiva et al (2013).…”
Section: Pml and Haloclinementioning
confidence: 99%
“…P. ubique HTCC1062; Sun et al, 2011) indicate that these microorganisms, some of the most abundant heterotrophic bacteria in surface waters, have genes that encode for oxidation pathways of a variety of one-carbon compounds, and they possess the capacity for demethylation and C1 oxidation, but do not incorporate C1 as biomass. These findings suggest the important role of this assemblage in obtaining energy from these compounds, and in mediating dissolved organic carbon cycling into CO 2 in the upper ocean (Sun et al, 2011).…”
Section: Rates Of Methane Produced In Surface Watersmentioning
confidence: 99%
“…P. ubique HTCC1062; Sun et al, 2011) indicate that these microorganisms, some of the most abundant heterotrophic bacteria in surface waters, have genes that encode for oxidation pathways of a variety of one-carbon compounds, and they possess the capacity for demethylation and C1 oxidation, but do not incorporate C1 as biomass. These findings suggest the important role of this assemblage in obtaining energy from these compounds, and in mediating dissolved organic carbon cycling into CO 2 in the upper ocean (Sun et al, 2011). Neufeld et al (2008) demonstrated that active marine methylotrophs belonging to the Alphaproteobacteria and Gammaproteobacteria are associated with phytoplankton blooms in coastal environments, which in turn, and depending on the phytoplankton species, provide substrates for methylotrophs and mediate CH 4 production.…”
Section: Rates Of Methane Produced In Surface Watersmentioning
confidence: 99%